The role of discounting in bargaining with one-sided offers - Francesc Dilmé (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
This paper analyzes a continuous-time Coase setting with finite horizon, interdependent values, and different discount rates. Our full characterization of equilibrium behavior permits studying how patience shapes the bargaining outcome. We obtain that (i) the seller's commitment problem persists even when she is fully patient, (ii) making the seller more impatient may increase equilibrium prices, (iii) when adverse selection is not strong, the buyer is ex-post better off when he is more impatient, and (iv) when discounting is time-dependent, episodes where the seller or the buyer have a high discount rate feature a large probability of trade, but only periods with high buyer discounting lead to a fast price decline.
Keywords: C78; D82; 330; Bargaining; one-sided offers; different discount factors